1999
DOI: 10.1115/1.2832691
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Keyhole in PAW of Aluminum Alloys

Abstract: This paper presents a technique for front image sensing of the weld pool in variable polarity plasma arc welding of aluminum alloys, and describes the determination of the geometrical size of the keyhole for subsequent real-time feedback control of a full penetration weld. Image formation occurs when the arc light reflects off the concave mirror-like surface of the depressed keyhole weld pool, and passes through a band-pass filter onto the image sensor. The image of the visual keyhole (nominal keyhole) is a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It is found in our previous research work that the image sensing has a pretty good potential in monitoring the stability of the welding pool [5][6][7][8]. However, the field of view of the keyhole from the front side of the workpiece is very limited because the standoff distance of the welding torch is only about 5.0 mm, while the diameter of the welding torch is about 50.0 mm.…”
Section: Image Sensingmentioning
confidence: 99%
“…It is found in our previous research work that the image sensing has a pretty good potential in monitoring the stability of the welding pool [5][6][7][8]. However, the field of view of the keyhole from the front side of the workpiece is very limited because the standoff distance of the welding torch is only about 5.0 mm, while the diameter of the welding torch is about 50.0 mm.…”
Section: Image Sensingmentioning
confidence: 99%
“…With the advancements in image acquisition technology, there is significant potential in using image sensing for monitoring weld pool stability [16][17][18][19]. Xu et al observed that when the keyhole weld becomes destabilised, the arc egress side of the trailing flame is offset at an angle, which is a result of changes in the weld pool morphology [20].…”
Section: Introductionmentioning
confidence: 99%
“…With the advancements in image acquisition technology, there is significant potential in using image sensing for monitoring weld pool stability [1619]. Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and co-workers [22][23][24][25][26][27][28][29][30][31][32][33][34] studied sensing and real time control of the weld quality for the VPPAW process, and obtained the geometrical shape of the front side keyhole pool. Lei 16,[35][36][37] and Zheng 16 investigated the effects of welding process parameters on the shape of the weld and discussed the formation mechanism for the VPPAW weld.…”
Section: Introductionmentioning
confidence: 99%